2021
DOI: 10.1007/s10029-021-02465-x
|View full text |Cite
|
Sign up to set email alerts
|

SubCutaneous OnLay endoscopic Approach (SCOLA) for midline ventral hernias associated with diastasis recti

Abstract: Introduction Minimally invasive surgery for diastasis recti has gained attention in the recent past, with several reports with different names and particularities being suggested by the authors. SCOLA (Subcutaneous OnLay endoscopic Approach) is an example of this technique, described here in standardized technique. Description of the technique Basic steps to perform the procedure are detailed, beginning with patient and surgical team positioning, including trocar placement and tips and tricks of the subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It carries with it a higher seroma rate as compared to other techniques. [ 22 ] Our experience with the technique is limited, as we prefer to place the mesh in retromuscular plane. MILOS/eMILOS approach described by Schwarz et al .…”
Section: Discussionmentioning
confidence: 99%
“…It carries with it a higher seroma rate as compared to other techniques. [ 22 ] Our experience with the technique is limited, as we prefer to place the mesh in retromuscular plane. MILOS/eMILOS approach described by Schwarz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported minimally invasive surgical techniques for DRA, including the Venetian blind technique, 1 intracorporeal suture and underlay mesh repair, SubCutaneous OnLay endoscopic Approach (SCOLA), 7 pre-aponeurotic endoscopic repair (REPA), 8 the Trentino Hernia Team (THT) technique, 9 suturing the rectus sheath with a linear stapler, and placing retrorectus mesh. However, the long-term outcomes of these techniques are unknown, and it is unclear which is the best procedure for DRA repair.…”
Section: Discussionmentioning
confidence: 99%
“…The rectus abdominis muscles are directly in reach of the surgeon for repair through the incision, which is commonly performed along the midline of the abdomen as compared to laparoscopic surgery, where there are some small incisions through which this whole procedure is performed. The surgery site is viewed with the help of a laparoscope and other specialized instruments, which are required to be placed through other incisions for closing rectus diastasis [24][25][26][27].…”
Section: Rectus Diastasismentioning
confidence: 99%